2004
DOI: 10.1074/jbc.m311919200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Has Intrinsic Kinase Activity

Abstract: Tissue transglutaminase (TG2) is a ubiquitous enzyme that cross-links glutamine residues with lysine residues, resulting in protein polymerization, cross-linking of dissimilar proteins, and incorporation of diamines and polyamines into proteins. It has not previously been known to have kinase activity. Recently, insulin-like growth factor-binding protein-3 (IGFBP-3) has been reported to be phosphorylated by breast cancer cell membranes. We purified the IGFBP-3 kinase activity from solubilized T47D breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(83 citation statements)
references
References 26 publications
1
81
0
1
Order By: Relevance
“…We have recently found that IGFBP3 has a role in insulin secretion (Nguyen et al 2011). Moreover, we have shown that ATP and Ca 2C reciprocally regulate transamidation and kinase activities of TG2 (Mishra & Murphy 2004). ATP facilitates kinase activity and has an inhibitory effect on transamidation activity, whereas Ca 2C has an opposite effect (Mishra & Murphy 2004, Mishra et al 2007a.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently found that IGFBP3 has a role in insulin secretion (Nguyen et al 2011). Moreover, we have shown that ATP and Ca 2C reciprocally regulate transamidation and kinase activities of TG2 (Mishra & Murphy 2004). ATP facilitates kinase activity and has an inhibitory effect on transamidation activity, whereas Ca 2C has an opposite effect (Mishra & Murphy 2004, Mishra et al 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…5, 10 mM magnesium chloride, [g-32 P]ATP (25 mCi/ml)) for 30 min at 30 8C as described previously (Mishra & Murphy 2004, Mishra et al 2006. The reaction was stopped by the addition of SDS-PAGE sample buffer and the samples were boiled for 5 min.…”
Section: In Vitro Kinase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…3 Recently a protein disulphide isomerase and a kinase activity of TG2 have also been described. 4,5 To assess the biological role, TG2 knockout mice have been generated. These mice show impaired glucose-stimulated insulin secretion and intolerance after glucose loading.…”
mentioning
confidence: 99%